Positron emission tomography/computed tomography in locally advanced breast cancer - Ozkan, E. (Experimental Oncology, 2013)
Locally advanced breast cancer (LABC) is a relatively small group of breast cancer, but is significant because it carries a higher risk of locoregional recurrence and distant metastasis. The accepted approach for these patients is neoadjuvant chemotherapy before surgery as determining the response to therapy in the early stages is of critical importance in respect of the approach taken to the disease. Positron emission tomography/computed tomography (PET/CT) using fluorine-18-fluorodeoxyglucose (18F-FDG) is currently used for staging, restaging and response monitoring in breast cancer. The areas of use of FDG PET/CT in LABC can be summarised as the evaluation of response to neoadjuvant chemotherapy in the early stage in particular, and the determination of unexpected areas of metastasis not detected by standard imaging techniques. There are current ongoing studies on promising new PET radiopharmaceuticals apart from FDG.